The effect of boron oxide on phosphate ion released from borosilicate glass in seawater - Yusof, Nurul Fariha (Trans Tech Publications, 2016)
Glasses in the system [wt.%: (55-x)% SiO2-(15+x)% B2O3-15% P2O5-10% Na2CO3-5% Fe2O3] where 15 ≤ x ≤ 40 % have been prepared with the different amount (35-55 wt%) of boron oxide. The compositions were constant by fixing the P2O5 at 15 wt%, Na2CO3 at 10 wt% and Fe2O3 at 5 wt%. Phosphate is the nutrients for algae growth in seawater and boron act as catalyst for phosphate ion release. The objective of this study is to determine the effect of boron oxide on phosphate ion released from borosilicate glass in seawater. The glass was melted in the alumina crucible for 2 hours at 1300 °C. The obtained glass was shattered into small pieces and sieved at mean size of 710 μm. The samples were immersed in seawater under dynamic condition by stirring at 310 rpm. Each of the water samples was taken 6 times between 75 minutes and analyzed using Discrete Auto Analyzer. The functional group and morphological characterization on the glass surface were investigated using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). Analyses of the data indicated that the amount of 50 wt% boron was the best and optimum for the phosphate ion release which is 126.53 ppm.